Differences in Arrhythmia Detection Between Harvard Step Test and Maximal Exercise Testing in a Paediatric Sports Population - Massimiliano Bianco; Fabrizio Sollazzo; Riccardo Pella; Saverio Vicentini; Samuele Ciaffoni; Gloria Modica; Riccardo Monti; Michela Cammarano; Paolo Zeppilli; Vincenzo Palmieri (Journal of Cardiovascular Development and Disease)
BACKGROUND: Sport practice may elevate the risk of cardiovascular events, including sudden cardiac death, in athletes with undiagnosed heart conditions. In Italy, pre-participation screening includes a resting ECG and either the Harvard Step Test (HST) or maximal exercise testing (MET), but the relative efficacy of the latter two tests for detecting arrhythmias and heart conditions remains unclear. METHODS: This study examined 511 paediatric athletes (8–18 years, 76.3% male) without known cardiovascular, renal, or endocrine diseases. All athletes underwent both HST and MET within 30 days. Absolute data and data relative to theoretical peak heart rates, arrhythmias (supraventricular and ventricular) and cardiovascular diagnoses were collected. RESULTS: HST resulted in a lower peak heart rate than MET (181.1 ± 9.8 vs. 187.5 ± 8.1 bpm, p < 0.001), but led to the detection of more supraventricular (18.6% vs. 13.1%, p < 0.001) and ventricular (30.5% vs. 22.7%, p < 0.001) arrhythmias, clustering during recovery (p = 0.014). This pattern was significant in males but not females. Among athletes diagnosed with cardiovascular diseases (22.3%), HST identified more ventricular arrhythmias (26.3% vs. 18.4%, p = 0.05), recovery-phase arrhythmias (20.2% vs. 14.0%, p = 0.035), and polymorphic arrhythmias (6.1% vs. 1.8%, p = 0.025). CONCLUSIONS: HST detects arrhythmias more effectively than MET in young male athletes, especially during recovery. More ventricular arrhythmias were highlighted even in athletes with cardiovascular conditions.